Investigation of Prosocial Behaviors and Sports Characters of Sports High School Students - Muhammed Enes TARIM; Rüstem ORHAN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The concept of prosocial behavior began to take place in the field of social psychology after the 1960s. Prosocial behaviors that benefit people and society, such as helping others, cooperating, empathizing and donating, are explained as a concept used synonymously with positive social attitudes, seen as positive in terms of purpose and outcome, and evaluated in the opposite sense to anti-social situations. In this study, the prosocial behaviors and sportive character structures of students studying at a sports high school were examined and the relationship between them was investigated. 328 sports high school students continuing their education in Karaman, Kırıkkale, Kırşehir, Konya and Sivas contributed to the study. The data were obtained using the ‘Sport Character Scale’ prepared by Chang-Yong Jang (2013), adapted into Turkish by Görgüt and Tuncel (2017), the ‘Adolescent Prosociality Scale’ created by Ata and Artan (2020), and the personal information form developed by the researcher. As a result of the study, it was determined that there was a significant relationship between the sub-dimensions of the Sports Character Scale (SCS) and the variables of age, city of residence, parental togetherness and family attitude, and within the scope of the sub-dimensions of the Adolescent Prosocial Scale (APS), there was a significant relationship between the city of residence and sports branch variables. In the internal prosociality sub-dimension, the mean score of the girls was higher than the boys. In addition, the mean of the anti-social sub-dimension of the sports high school students was found to be higher than the other variables, and the mean of the honesty and compassion sub-dimensions was found to be lower. The mean of the internal prosocial sub-dimension of the APS variables was found to be higher than the mean of the external prosocial sub-dimension. When the correlation results of the SCS and APS were examined, it was evaluated that there was an interaction between the sub-dimensions of the two scales. As a result, it is thought that positive changes will be provided in the sportive character structures of the sports high school students and that their prosocial behavioral tendencies will increase by cooperating with humanitarian aid institutions and organizations.